Relief Package: Stabilisation of Expectations - Michael Hüther (Wirtschaftsdienst)
Abstract The sharp rise in energy prices represents a considerable structural risk to the German economy. Deindustrialisation has become a veritable threat. The government’s economic policy needs to establish positive expectations for energy costs in the medium term through interventions in the gas and electricity markets. As in the COVID-19 pandemic, politicians should give companies generous deferral options for income and sales taxes and partially reimburse advance payments. The elimination of the cold progression does not constitute a tax relief and does not contradict the support of liquidity-weak households with targeted transfers, as both measurements are necessary for different reasons.